2022
DOI: 10.7150/thno.64252
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of cellular components between platelets and tumor cells: impact on tumor cells behavior

Abstract: Background: Platelets are active players in tumorigenesis, although the exact interactive mechanisms and their direct impact on tumor cells remain largely unknown. Methods: Bidirectional transference of lipids, proteins and RNA between platelets and tumor cells and its impact on tumor cell behavior and tumor process are analyzed in this work. Phenotypic, genetic and functional modifications induced by platelets were analyzed both in tumor cell lines and in circulating tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…An important mechanism for CTC survival is the formation of heterotypic clusters with different cells, such as MDSCs (Sprouse et al, 2019), stromal cells like fibroblasts (Hurtado et al, 2020) and/or neutrophils (Szczerba et al, 2019), macrophages (Hamilton and Rath, 2017), and DCs (Wei et al, 2019b). Furthermore, platelets also play a role in the immune evasion by facilitating the escape of CTCs from MHC class I-mediated recognition by NK and T cells by the transfer of MHC class I onto the tumor cell surface (Placke et al, 2012a;Rodriguez-Martinez et al, 2022). In addition, platelets provide CTCs with a coating shield that helps their survival from the physical stress in the blood and from anoikis (Lucotti and Muschel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An important mechanism for CTC survival is the formation of heterotypic clusters with different cells, such as MDSCs (Sprouse et al, 2019), stromal cells like fibroblasts (Hurtado et al, 2020) and/or neutrophils (Szczerba et al, 2019), macrophages (Hamilton and Rath, 2017), and DCs (Wei et al, 2019b). Furthermore, platelets also play a role in the immune evasion by facilitating the escape of CTCs from MHC class I-mediated recognition by NK and T cells by the transfer of MHC class I onto the tumor cell surface (Placke et al, 2012a;Rodriguez-Martinez et al, 2022). In addition, platelets provide CTCs with a coating shield that helps their survival from the physical stress in the blood and from anoikis (Lucotti and Muschel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study suggested that prostate CTCs cocultured with platelets showed decreased EpCAM expression levels but elevated platelet marker CD61, accompanied by a higher proliferation rate during EMT. The results indicated that CD61, rather than EpCAM, might be an alternative diagnostic marker in this situation [ 107 ].…”
Section: Applications Of Epcam In Clinical Oncologymentioning
confidence: 99%
“…Tumor-Educated Platelets (TEPs) reprogram the behavior of CTCs via a direct interaction accompanied by exchanging RNA, lipids, and proteins (i.e., beta-3 integrin marker CD61) [ 206 ]. This trafficking event creates a supportive microenvironment for CTCs and facilitating their immune evasion via protecting them from natural killer cells [ 207 ].…”
Section: Liquid Biopsy Biomarkers In Prostate Cancermentioning
confidence: 99%
“…This trafficking event creates a supportive microenvironment for CTCs and facilitating their immune evasion via protecting them from natural killer cells [ 207 ]. The ability of platelets to alter tumor cells’ phenotypes and genetic content promote cell growth and plasticity [ 206 ]. During the course of tumor metastases initiation, TEPs facilitate EMT to lead the tumor towards metastases [ 206 ].…”
Section: Liquid Biopsy Biomarkers In Prostate Cancermentioning
confidence: 99%